The Legality of Price Rounding in Sale and Purchase Transaction under Indonesian and Islamic Law - Arifpadilah, Pajri; Hidayah, Nur Putri (Indonesian Comparative Law Review, 2025)
The need for easiness in making transaction has resulted in a unique method of payment known as price rounding system. This system is frequently applied in the transaction of various goods, including vegetables, foods, and clothing.  In spite of its practical advantage, there is a potential economic loss suffered by the buyers or consumers, especially when the sellers tend to round the price up. Consequently, the question on its legality arises. This study analyzes the legality of transaction applying the price rounding system from the perspective of Indonesian and Islamic law. This normative legal research employs both statutory and conceptual approaches. The result of this study indicates that the price rounding practice is allowed under Indonesian law as far as the buyer agrees to pay the item at the rounded price. On the other side, such a practice is prohibited under Islamic law since it violates the Qur’anic provisions. However, there is an opportunity to continue such a practice in particular places where the local custom (‘Urf) in those places tolerate it. The authors suggest that consumers should pay more attention on such a practice to avoid any manipulation committed by the sellers.